Dormant Sprays for Asian Citrus Psyllid Management - Jawwad Qureshi (EDIS, 2020)
Several studies have documented the positive effects of controlling the Asian citrus psyllid (ACP, Figure 1) for citrus tree health and sustainability in Florida. The mature blocks established before and after the discovery of huanglongbing (HLB) in 2005 continue to benefit from psyllid control.